Perbandingan Efektivitas Modalitas Radiologi Dalam Deteksi Dini Kanker Payudara - Yudia Nurul Eliza; Febie Irsandy Syahruddin; Abdul Syukur Kuddus (2026)
Cancer is one of the leading causes of death worldwide. Breast cancer is one of the more common in women, which appears as a malignant tumor in breast tissue consisting of mammary glands, milk ducts, connective tissue, and adipose. This study aimed to compare the effectiveness of radiologic modalities in the early detection of breast cancer, focusing on grayscale ultrasound, mammography and MRI examinations. The research method included a literature review of previous studies that discussed the comparative effectiveness of radiologic modalities in the early detection of breast cancer. The analysis showed that mammography, ultrasound and MRI are the imaging methods used to detect breast cancer, with each having advantages and disadvantages in terms of sensitivity and specificity. MRI has the highest sensitivity, especially for detecting small tumors and in women with dense breast tissue, but has lower specificity than mammography. Mammography, despite the use of radiation, is effective for early detection, especially in women with high risk factors. Ultrasound is often used as a follow-up examination or to evaluate lumps detected on mammogram.